Achieving carbon neutrality through green technological progress: evidence from China. (February 2023) - Cai, Jinyang; Zheng, Huanyu; Vardanyan, Michael; Shen, Zhiyang
Abstract: Climate change related environmental problems are pushing a constantly growing number of countries to set carbon neutrality goals. Increasing reliance on ecologically friendly technologies is widely considered to be a crucial means of achieving this objective. Many existing studies measure environmental performance using carbon dioxide emissions, or carbon sources, but do not consider the amount of carbon offset through sequestration in carbon sinks. We define carbon neutrality performance as the difference between the carbon sinks and carbon sources and quantify its relationship with green technological innovation, approximated using the notion of environmental productivity. We rely on the Chinese province-level data from 2001 to 2019 and demonstrate that green innovation can significantly facilitate the attainment of carbon neutrality objectives. Our mediation model suggests that low-carbon innovation can help reach carbon neutrality by decreasing net emissions directly, but also by inhibiting the urbanization rate and promoting renewable energy generation. Our analysis helps shed light on the possible strategies that policymakers in China and other developing countries can follow to realize their carbon neutrality aspirations. Highlights: We compute the total factor productivity using the DEAmodel. We examine the green technology progress in China. We use the benchmark regression model and intermediary effect model. The green technological progress may promote carbon neutrality.